Islet Autoantibody Positive Offspring of Mothers with Type 1 Diabetes have Higher Functional Beta-cell Capacity than Those of Fathers with Type 1 Diabetes - Talsi, Katariina (My University, 2026)
Objective The risk of type 1 diabetes is lower among children of mothers versus fathers with type 1 diabetes. Among mothers with type 1 diabetes, intrauterine hyperglycemia may induce beta-cell proliferation for the fetus and increase their functional beta-cell mass. We investigated whether parental type 1 diabetes affects beta-cell function in the offspring. Research Design and Methods We analyzed first-phase insulin response (FPIR) in intravenous glucose tolerance tests in children with increased HLA-conferred risk of type 1 diabetes. In total, 1777 FPIRs were measured in offspring of 21 mothers and 33 fathers with type 1 diabetes and 523 children without a first degree relative (FDR) with type 1 diabetes (general population). We included FPIRs measured after emergence of islet autoantibodies. We modeled log-transformed FPIR (log-FPIR) using linear mixed model and compared FPIRs in the three FDR groups. Results At seroconversion, children with maternal type 1 diabetes had higher log-FPIR (p=0.005) and children with paternal type 1 diabetes had lower log-FPIR (p=0.03) compared to general population. At multipositivity the results were similar. After seroconversion the decrease in log-FPIR was greater in the children with maternal (p=0.004) and paternal (p=0.02) type 1 diabetes compared to general population. After multipositivity log-FPIR decreased in all three groups, but the decay was faster in children with maternal (p=0.004) or paternal (0.02) type 1 diabetes than in general population. Conclusions At seroconversion for islet autoimmunity and at multipositivity children with maternal type 1 diabetes have higher FPIR compared to those with paternal type 1 diabetes.